2006
DOI: 10.1002/eat.20288
|View full text |Cite
|
Sign up to set email alerts
|

Familial and sociopsychopathological risk factors for suicide attempt in bulimic and in depressed women: Prospective study

Abstract: Sociopsychopathological risk factors for suicide attempts in the BNG and MDG appear to vary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Ten (Ayalon and Shiovitz-Ezra, 2011;Bonner and Rich, 1988;Gallagher et al, 2014 T1-T3;Hom et al, 2019;Joling et al, 2018;Lasgaard et al, 2011;McGraw, 2008;Nickel et al, 2006;Stolz et al, 2016;Wichstrøm, 2009) of the 15 studies (20 analyses) that recruited predominantly female participants (>50% female participants) found loneliness to be a significant predictor of later SIB compared to three of the seven studies (eight analyses) that contained predominantly male participants.…”
Section: Gendermentioning
confidence: 99%
See 2 more Smart Citations
“…Ten (Ayalon and Shiovitz-Ezra, 2011;Bonner and Rich, 1988;Gallagher et al, 2014 T1-T3;Hom et al, 2019;Joling et al, 2018;Lasgaard et al, 2011;McGraw, 2008;Nickel et al, 2006;Stolz et al, 2016;Wichstrøm, 2009) of the 15 studies (20 analyses) that recruited predominantly female participants (>50% female participants) found loneliness to be a significant predictor of later SIB compared to three of the seven studies (eight analyses) that contained predominantly male participants.…”
Section: Gendermentioning
confidence: 99%
“…Three (Junker et al, 2017;Nickel, 2006;Wichstrøm, 2009) of the seven studies (8 analyses) which explored any form of suicidal behaviour found loneliness to be a significant predictor. Studies which reported a significant association were all those which explored self-harm as the outcome.…”
Section: Narrative Summary Of Study Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 A one-year prospective study identified laxative use and a history of sexual abuse as the most significant risk factors for SA in the BN group. 20 However, the above mentioned studies have some limitations. In the first prospective study, 19 patients with AN of the restricting subtype (AN-R) and those with AN-B/P were grouped under the diagnosis of AN.…”
Section: Introductionmentioning
confidence: 99%
“…This limits the conclusions that can be drawn from that study since the two subtypes of AN differ substantially in terms of suicidality. The second one 20 recruited patients through advertisement, had a short follow-up length, and had a broad definition of SA. The other studies had a low to moderate number of participants (n 5 150-495), a limited number of variables examined, or no distinction between types of ED.…”
Section: Introductionmentioning
confidence: 99%